ANALISIS KINERJA MANAJEMEN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN PERBANKAN TAHUN 2020-2023 - Nyale, M Hendri Yan; Firdauza, Cayla Alifia (Jurnal Riset Akuntansi Politala, 2025)
This study aims to analyze management performance on sustainability report disclosure in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. Using purposive sampling technique, this study involved 25 companies, resulting in a total of 100 samples. The normality test shows that the data meets the assumption of normality. The analysis shows taht profitability has a significant positive effect on sustainability report disclosure. On the other hand, leverage has a significant negative influence, and company size has a significant positive influence on sustainability report disclosure.